Keberadaan Klausul Yang Tidak Dapat Diubah (Unamendable Provisions) Sebagai Identitas Konstitusi - Ika Kurniawati (Universitas Islam Indonesia, 2022)
Unamendable provisions are provisions set in order to limit the constitutional amendments. There are unamendable provisions that are implied or affirmed directly by the Constitution and there are those that may appear in the future should there be a dispute over the constitutional amendments. The concept of constitutional identity is always associated with unamendable provisions. The problems raised in this research are, first, how is the arrangement of unamendable provisions as constitutional identity in the 1945 Constitution? and second, what is the authority of the People's Consultative Assembly (MPR) in constitutional amendments to the Constitution? This is a juridical normative research, which the results of the research conclude that first, the existence of unamendable provisions as a constitutional identity must be expressly stated in the Constitution. Unamendable provisions are implicitly contained in Article 37 paragraph (5) of the 1945 Constitution and in the basic agreement made by the founding fathers of the nation before amending the Constitution. Second, the MPR's authority to amend the constitution is actually limited by provisions called unamendable provisions. This provision is contained in Article 37 paragraph (5) of the 1945 Constitution and is contained in the basic agreement which since the beginning of Indonesia's independence has been established by the nation's founders as a limiting provision in amending the constitution. Although, the MPR has a very large authority given by the 1945 Constitution in amending the constitution, but in carrying it out the MPR must be accompanied by good faith and political goodwill.Key Words: Constitutional identity; unamendable provision; 1945 constitution Abstrak Ketentuan yang tidak dapat diubah (unamendable provisions) merupakan ketentuan dalam membatasi amandemen konstitusi. Unamendable provisions ada yang tersirat ditunjukkan langsung oleh konstitusi dan adapula yang muncul dikemudian hari apabila terdapat perselisihan terhadap amandemen konstitusi. Konsep identitas konstitusi selalu dikaitkan dengan unamendable provisions.Permasalahan yang diangkat dalam penelitian ini, pertama, bagaimana pengaturan ketentuan yang tidak dapat diubah (Unamendable Provisions) sebagai identitas konstitusi dalam Undang-Undang Dasar 1945? dan kedua, bagaimana kewenangan Majelis Permusyawaratan Rakyat (MPR) dalam amandemen konstitusi secara konstitusional?. Penelitian ini bersifat yuridis normatif, hasil dari penilitian menyimpulkan bahwa, pertama, keberadaan ketentuan yang tidak dapat diubah (unamendable provisions) sebagai identitas konstitusi harus secara tegas dinyatakan dalam konstitusi. Unamendable provisons secara tersirat terdapat dalam Pasal 37 ayat (5) UUD 1945 dan dalam kesepakatan dasar yang dibuat oleh pendiri bangsa sebelum mengubah konstitusi. Kedua, kewenangan MPR untuk mengubah konstitusi sejatinya dibatasi oleh ketentuan yang disebut unamendable provisions. Ketentuan ini terdapat dalam Pasal 37 ayat (5) UUD 1945 serta terdapat dalam kesepakatan dasar yang sejak awal kemerdekaan Indonesia telah ditetapkan oleh pendiri bangsa sebagai ketentuan pembatas dalam mengamandemen konstitusi. Meskipun, kewenangan MPR yang sangat besar diberikan oleh UUD1945 dalam mengamandemen konstitusi, tetapi dalam melaksanakannya MPR harus dibarengi dengan itikad baik dan political goodwill.Kata-kata Kunci: Identitas konstitusi; unamendable provision; Undang-Undang Dasar Tahun 1945